N‐Confused Porphyrin Metal Complexes with an Axial Pyridine Directly Tethered from an Inner Carbon: A Bioinspired Ligand as a Versatile Platform for Catalysis. Issue 2 (22nd January 2018) - Miyazaki, Takaaki; Yamamoto, Takaaki; Mashita, Shunichi; Deguchi, Yuya; Fukuyama, Kazuki; Ishida, Masatoshi; Mori, Shigeki; Furuta, Hiroyuki
Abstract : Bioinspired pentadentate ligand N‐confused porphyrin (NCP) bearing a 2‐mercaptopyridine group and its Ru II and Co III complexes were synthesized. Their structures were revealed by single‐crystal X‐ray crystallographic analysis. Installation of an axial thiopyridine ligand shifts the redox potentials negatively and enhances the catalytic activity largely, which was demonstrated in the cyclopropanation reaction using the Co complex. Abstract : Bioinspired pentadentate ligand N‐confused porphyrin (NCP) bearing a 2‐mercaptopyridine group and its Ru II and Co III complexes were synthesized. Their structures were elucidated by single‐crystal X‐ray analysis. An axial 2‐thiopyridine ligand shifts the redox potentials negatively and enhances the catalytic activity of the Co complex for cyclopropanation.